Reestructuración técnica en la línea de ensamble montaje ‘A’ de la compañía Marcopolo S.A. (2018)
In the project presented below a company dedicated to the manufacture of large and small buses; For the purpose of this work, the large bus line Paradiso 1200 G7 was taken as a reference, with the aim of defining the different problems that arise in the area such as the delay in the arrangement of materials to assemble the bus, lack of synchronization with sub-assembly workshops, change in production orders, lack of standardization in process times and lack of documentation in the work methods that are currently being executed; taking into account this panorama.